Experiences with Railway Regulation in Great Britain and the Czech Republic – Round Table Report - Chris Nash; Zdeněk Tomeš; Monika Jandová (Review of Economic Perspectives, 2015)
The aim of the Round Table was to compare British and Czech experiences with railway regulation and competition introduction and to determine which lessons can be learnt. Special attention was paid to the question of whether the very complex British reform can be an inspiration for further liberalisation of the railway sector in the Czech Republic or whether there are any reform mistakes that are best avoided. Based on two introductory presentations and subsequent plenary discussion, some consensus emerged. The participants agreed that there is no one-size-fits-all solution to railway regulation and that the introduction of competition should take into account the different circumstances of a particular country. Franchising in passenger operations in Britain successfully stimulated demand but also increased costs to the industry, so its implementation should be completed with care. It seems very unlikely that open-access competition would be a viable solution for the whole passenger rail market because it is limited to a few commercially attractive routes, and as Czech experience suggests, it creates many new problems. Finally, it was confirmed that a strong and dedicated regulator is needed in a newly liberalised environment in order to solve many emerging conflicts and disputes.
Keywords: 330